(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article provides a comprehensive analysis of the age-dependent risks and complications associated with contracting viral hepatitis. It examines how the likelihood of infection varies across different age groups and explores the diverse complications that may arise. By reviewing existing literature, this study aims to shed light on the importance of tailored prevention strategies and targeted management approaches for various age cohorts.